1998
DOI: 10.1002/(sici)1097-4644(19980915)70:4<517::aid-jcb8>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of tissue inhibitor of metalloproteinases‐3 gene expression by TGF‐β in articular chondrocytes is mediated by serine/threonine and tyrosine kinases

Abstract: The balance between matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) regulates extracellular matrix turn-over in normal animal development, cancer cell metastasis, atherosclerotic plaque rupture and erosion of arthritic cartilage. Transforming growth factor beta (TGF-beta), an inducer of matrix synthesis, potently enhances mRNA and protein of a recently characterized MMP inhibitor, TIMP-3, in bovine articular chondrocytes. We examined the implication of protein kinases in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…However, the level of cystatin C mRNA was unchanged (Figure 4b), consistent with the constitutive nature of the cystatin C promoter (29). To explore further the regulation of cystatin C expression in SMC, we also tested a cytokine previously reported to induce other classes of protease inhibitors, TGF-β 1 (30)(31)(32). TGF-β 1 (5 ng/mL) did not change the level of cathepsin S mRNA or protein or of cystatin C mRNA (Figure 4b).…”
Section: Figuresupporting
confidence: 67%
“…However, the level of cystatin C mRNA was unchanged (Figure 4b), consistent with the constitutive nature of the cystatin C promoter (29). To explore further the regulation of cystatin C expression in SMC, we also tested a cytokine previously reported to induce other classes of protease inhibitors, TGF-β 1 (30)(31)(32). TGF-β 1 (5 ng/mL) did not change the level of cathepsin S mRNA or protein or of cystatin C mRNA (Figure 4b).…”
Section: Figuresupporting
confidence: 67%
“…The MMPs are first synthesized as inactive zymogens that may be activated via cleavage of an activation propeptide by various membrane-type metalloproteases (MMPs) (43), by soluble MMPs that have already been activated (44), or via furin-dependent intracellular processing (45). MMPs are themselves transcriptionally regulated by various growth factors and cytokines (46,47). After activation, protein inhibitors known as the tissue inhibitors of metalloproteases (42) may inactivate the MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…1). Thus, there is considerable interest in understanding factors regulating TIMP-3 levels, and it has been shown that transcription of TIMP-3 can be increased by the histone deacetylase SirT1 (10) and growth factors such as TGF␤ (11) and oncostatin M (12) and reduced by promoter methylation (13). Translation of TIMP-3 can be reduced by miR-21 (14), miR-221 and miR-222 (15), miR-181b (16), and miR-206 (17).…”
Section: Tissue Inhibitor Of Metalloproteinases-3 (Timp-3) Plays a Kementioning
confidence: 99%